ANALISIS TINGKAT KESEHATAN BANK UMUM SYARIAH SEBELUM DAN SESUDAH TERDAFTAR DI BEI - Yetri Martika Sari (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2019)
This study aims to assess the soundness of sharia commercial banks before and after being registere don the Indonesian stock exchange using the Risk-Based Bank Rating (RBBR) method which is stipulated in the OJK regulation No.8/POJK.03/2014 concerning the assessment of the soundness level of sharia commercial banks and sharia businessunits. The object of this research are sharia commercial banks registered on the Indonesian stock exchange (IDX). The sampling technique in this study used purposive sampling with the criteria of sharia commercial banks which was conducting an initial public offering in 2018. Two samples were obtained for this research, namely BRIS and BTPNS. The analytical techniques in this study were descriptive quantitative using four RBBR factors namely risk profile (NPF and FDR), GCG, profitability (NOM and ROA), andcapital (CAR). The resultsofthis study on the soundness of the bank before and after being listed on the IDX did not indicate a difference in the health rating of the banks both BRIS and BTPNS. the results of a comparison of the performance of BRIS and BTPNS seen from the four RBBR factors showed tha tBTPNS's performance was better than BRIS's performance.